Topoi and Toponyms: The Rhetoric of the City in Isa 1 and Assyrian Imperial Practices - Boyd, Samuel L. (Zeitschrift für die alttestamentliche Wissenschaft, 2023)
The influence of Assyrian ideology on First Isaiah has received extensive treatment over the past few decades. I present another possible datum to explain a rhetorical argument that unfolds in Isa 1:21-28 through the addition of the later supplement in vv. 29-31, namely the shift in Jerusalem from being labeled a »faithful city« to an »unfaithful city«. In light of the political grounding of the passage, the historical backdrop of the intermittent Assyrian practice of changing the toponyms of subjugated cities becomes more transparently important for unlocking the meaning and significance of this passage.